(untitled) - Schwartz, Mel M. (Upper Saddle River, N.J., 1997)
This second volume on composite materials fabrication, processing ,and future reinforced composite material systems seeks to cover this vast field of materials and engineering
Keywords: Composite materials,Vật liệu tổng hợp